Influence of Organization Based Self-Esteem, Role Breadth Self-Efficacy and Voluntary Learning Behavior on Perceived Employability - Sohail, Hafsa; Tahir, Aqsa (iRASD Journal of Management, 2023)
The study examines the impact of organizational-based self-esteem, role breadth self-efficacy, and voluntary learning behavior on perceived employability. Perceived employability is determined by an individual's capabilities and competencies, which enhance their employment opportunities in the future. The study collected data through a survey of employees in the banking sector in Karachi, using SPSS tools to analyze the effects of the antecedents of perceived employability and voluntary learning behavior. The research aimed to investigate the relationship between self-concepts and voluntary learning behavior, highlighting the critical influence of employees on both antecedents. The findings of this study could improve employee performance and help develop specific abilities and skills required by employers, such as creativity and inspiration. The study emphasizes the importance of perceived employability in obtaining better employment opportunities and its impact on the Pakistani context.